What’s new in sleep disorders? Characteristics of sleep disorders according to ICD-11 - Górska, Karolina; Ścisło, Lucyna; Pluta, Judyta; Antoniak-Sobczak, Katarzyna; Fojcik, Joanna; Górski, Michał K. (Nursing Problems / Problemy Pielęgniarstwa, 2023)
Sleep is a key factor in daily human functioning and in maintaining good health. Various important physiological changes happen in all body systems and organs during sleep, chiefly due to functional changes in the autonomic and somatic nervous systems. Sleep disorders are a considerable issue in contemporary societies because they can have severe implications for health and well-being. Disrupted sleep duration and abnormal sleep quality can both lead to sleep disorders. The disorders include insomnia, hypersomnia, sleep disorders in attention deficit hyperactivity disorder, sleep-wake rhythm disorders, sleepwalking, and behavioural REM sleep disorders. This article presents the latest diagnostic criteria and general characteristics of the disorder. The latest scientific reports on sleep disorders and their consequences are also presented. This article aims to describe the crucial significance of sleep to human life and to define sleep disorders based on the International Classification of Diseases, 11th Revision (ICD-11).